PENUNTASAN BUTA AKSARA DI DUSUN PENANGGUNGAN DESA ROWO INDAH KECAMATAN AJUNG KABUPATEN JEMBER - Achmad Faisol (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2022)
Illiteracy eradication activities have been carried out for a long time, and until now there are still illiterates. One of the main reasons is that there are still elementary school dropouts who return to being illiterate, besides being forced to leave school for various reasons. The existence of an illiterate population is suspected to have contributed to the lack of success of the 9-year-old Fair, because if the parents of the child are illiterate, there is a tendency for their child to not go to school and even if school occurs they often repeat classes and even drop out of school. Completion of the 9-year Compulsory Basic Education (Wajar Dikdas) Program through the Literacy Education Program through Strategy Training. Learning to read can take the following steps: 1. Dissemination and promotion of the importance of 9-Year Basic Education. 9 years, through non-formal channels, 3. Consolidating with the local government to empower nonformal education institutions in accommodating the community's needs for education, 4. Providing educational services for community members who have not completed 9 years of Basic Education, especially those aged between 10 up to 44 years.